Hubungan Aktivitas Fisik dan Asupan Kalori Dengan Status Gizi Lebih Siswa SMA di Wilayah Kerja Puskesmas Teluk Dalam - Abraham Hamonangan H Hutabarat; Triawanti Triawanti; Ida Yuliana (Homeostasis, 2020)
Abstract: Obesity is excessive or abnormal fat accumulation in the body that can interfere with health. Riskesdas data for 2018, the prevalence of overweight and obese population aged 16-18 years in South Kalimantan Province reached 8.9% overweight and 3.2% obese. The study aims to determine the association of physical activity and calorie intake with the over nutritional status of high school students in the work area of the Teluk Dalam Health Center. The variables studied were physical activity and calorie intake. Analytic observational research methods with a case control approach. The research sample was students with over nutritional status and normal nutritional status based on data from the Teluk Dalam Puskesmas in Banjarmasin in the 2018 period. Sampling with simple random sampling. Data analysis using Kolmogorov Smirnov test. The results of this study in the case group contained 80.5% had mild activity, 19.5% moderate activity, 5.6% less calorie intake, 80.6% normal calorie intake, and 13.8% excessive calorie intake. While the control group contained 13.9% had mild activity, 83.3% moderate activity, 2.8% heavy activity, 22.2% less calorie intake, 75% moderate calorie intake, and 2.8% excessive calorie intake. The results of the Kolmogorov Smirnov test analysis showed that there was an association between physical activity and the nutritional status of high school students in the work area of the Teluk Dalam Health Center (p = 0,000) and there was no association between calorie intake and the nutritional status of the high school students in the work area of the Teluk Dalam Health Center (p = 0.699 ). Keywords: physical activity, calories intake, nutritional status, adolescents Abstrak: Obesitas adalah akumulasi lemak secara berlebihan atau abnormal dalam tubuh yang dapat mengganggu kesehatan. Data Riskesdas tahun 2018, prevalensi gemuk dan obesitas penduduk dengan umur 16-18 tahun di Provinsi Kalimantan Selatan mencapai 8,9% gemuk dan 3,2% obesitas. Penelitian bertujuan mengetahui hubungan aktivitas fisik dan asupan kalori dengan status gizi lebih siswa SMA di wilayah kerja Puskesmas Teluk Dalam. Metode penelitian observasional analitik dengan pendekatan case control. Sampel penelitian adalah siswa dengan status gizi lebih (kelompok kasus) dan status gizi normal (kelompok kontrol). Variabel yang diteliti adalah aktivitas fisik dan asupan kalori yang diambil dengan cara simple random sampling. Analisis data menggunakan uji kolmogorov smirnov. Hasil penelitian ini pada kelompok kasus terdapat 80,5% memiliki aktivitas ringan, 19,5% aktivitas sedang, 5,6% asupan kalori kurang, 80,6% asupan kalori normal, dan 13,8% asupan kalori berlebih. Pada kelompok kontrol terdapat 13,9% memiliki aktivitas ringan, 83,3% aktivitas sedang, 2,8% aktivitas berat, 22,2% asupan kalori kurang, 75% asupan kalori sedang, dan 2,8% asupan kalori berlebih. Hasil analisis uji Kolmogorov Smirnov menunjukkan terdapat hubungan antara aktivitas fisik dengan status gizi lebih siswa SMA di wilayah kerja Puskesmas Teluk Dalam (p=0,000) dan tidak terdapat hubungan antara asupan kalori dengan status gizi lebih SMA di wilayah kerja Puskesmas Teluk Dalam (p=0,699). Kata-kata kunci: aktivitas fisik, asupan kalori, status gizi, remaja